The KAJIAN KESESUAIAN EKOWISATA MANGROVE DI PERAIRAN BELAWAN - Mardame Pangihutan Sinaga; Ewin Handoco S; Tambos August Sianturi; Jhon Sufriadi Purba; Frans Willis Siregar (Abdi Jurnal Publikasi, 2023)
Community service was carried out on 27-28 October 2022 at SMP Negeri 3 Jorlang Hataran. The activity was carried out by introducing about protecting and caring for mangroves in Belawan waters to serve as ecotourism. The results obtained were that there were 10 types of mangroves located at 3 stations, namely Sonerattia alba, Avecennia offinalis, Avicennia alba, Bruguiera sexangula, Bruguiera cylindrica, Bruguiera gymnorrhiza, Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa and Ceriops tagal. The highest mangrove species were Bruguiera cylindrica and Rhizophora stylosa and the lowest were Sonerattia alba, Avecennia officinalis, Bruguiera sexangula, Rhizophora mucronata, Rhizopora apiculate, and Ceriops tagal.